Traditional Aquatic Symbols in Niyi Osundare’s Tender Moments (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
Many scholars focus on Niyi Osundare’s eco-poems as well as his socio-political views, that his love poems seem to have been neglected. Niyi Osundare uses various categories of images and symbols to explore a variety of themes in his poetry collections. A close look at the love poems of this renowned poet shows that he is a master at expressing the untold emotions between lovers. Love is a central theme in African poetry and gifted African poets like Osundare have found ways of expressing its intricacies in a symbolic perspective. This paper examines traditional aquatic symbols as vehicles through which Osundare expresses the emotion of love in his poetry collection entitled ‘Tender Moments’. The paper uses the qualitative research modalities of analytic and direct observation methods. The study is done using Sigmund Freud’s psychoanalytic theory, which allows the researcher to probe into the motives that drive writers to present their works in the manner they do.  This study enquires into the poet’s usage of these symbols in this special love collection and demonstrates how traditional aquatic symbols were used by the poet to buttress the theme of love. The paper concludes that these symbols were significant and effective in aiding the poet in his journey of expression.
Keywords: Traditional aquatic symbols; African poetry; African studies; Niyi Osundare; Tender Moments